Effects of Physalis angulata extracts on bleomycin-induced rat: analysis on lung inflammation and fibrosis - Wibowo, Suryo Anggoro Kusumo; Rumende, Cleopas Martin; Isbagio, Harry; Setiyono, Agus; Setiabudy, Rianto; Rachmadi, Lisnawati; Kertia, Nyoman (Medical Journal of Indonesia, 2025)
BACKGROUND Scleroderma is an immune-mediated connective tissue disease, with interstitial lung disease as one of its manifestations. Physalis angulata (P. angulata) or ciplukan has shown potential in treating fibrosis, but its role in preventing lung inflammation and fibrosis remains unknown. This study aimed to evaluate the effect of P. angulata extract in a bleomycin (BLM)-induced scleroderma rat. METHODS Sprague-Dawley rats were divided into 6 groups. For lung inflammation prevention, 3 groups received: (1) BLM only, (2) BLM+50 mg/kgBW P. angulata, and (3) BLM+100 mg/kgBW P. angulata. After 14 days, rats were sacrificed and bronchoalveolar lavage (BAL) leukocyte count, interleukin-6 (IL-6) levels, and lung injury score were assessed. For fibrosis prevention, another 3 groups received the same interventions and were sacrificed after 51 days. Fibrosis score, fibrosis area, hydroxyproline, transforming growth factor-beta (TGF-β), and matrix metalloproteinase-13 (MMP-13) levels were analyzed. BLM was administered subcutaneously, while P. angulata was given orally for 14 days. IL-6, TGF-β, and MMP-13 were measured by ELISA and hydroxyproline by colorimetric method. Mean differences and p-values were calculated using appropriate statistical tests. RESULTS P. angulata extract did not prevent lung inflammation, as there were no differences in BAL leukocyte count (p = 0.126), IL-6 levels (p = 0.173), or lung injury scores (p = 0.397) between the BLM-only group and those receiving P. angulata. The extract also did not prevent lung fibrosis, with no differences in fibrosis scores (p = 0.173), fibrosis area (p = 0.359), hydroxyproline (p = 0.295), TGF-β (p = 0.374), or MMP-13 (p = 0.088) levels among groups. CONCLUSIONS P. angulata extract did not prevent the development of lung inflammation or fibrosis.